Generalized Tikhonov-type regularization method for the Cauchy problem of a semi-linear elliptic equation - Zhang, Hongwu; Zhang, Xiaoju (Numerical algorithms, 2019)
This paper considers the Cauchy problem of a semi-linear elliptic equation and uses a generalized Tikhonov-type regularization method to overcome its ill-posedness. The existence, uniqueness, and stability for regularized solution are proven. Under an a priori bound assumption for exact solution, we derive the convergence estimate of H ö lder type for this method. An application of this method to the Cauchy problem of Helmholtz equation is discussed, and we investigate the stability and convergence estimates for different wave numbers. Finally, an iterative scheme is constructed to calculate the regularization solution, numerical results show that this method is stable and feasible.